2010
DOI: 10.1577/m09-094.1
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐Marking Reveals Emerging Self Regulation of the Chinook Salmon Population in Lake Huron

Abstract: All Chinook salmon Oncorhynchus tshawytscha stocked in Lake Huron during 2000–2003 were marked with oxytetracycline (OTC), fin clips, or a combination thereof to determine the relative contributions of natural reproduction and stocking to recruitment. Oxytetracycline administered in feed proved to be an effective, low‐cost method of marking spring fingerling Chinook salmon. Vertebrae proved to be suitable tissue for OTC detection, meeting standards for accuracy and reproducibility. Vertebrae were not suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…4 C and D) requires further research to determine if these services would benefit from restoration or are sufficiently resilient to stress that restoration is unnecessary. However, beach closings (17), sport fishery declines (18), and other types of foregone recreational opportunities suggest that stressor mitigation could indeed enhance service provisioning. For example, a number of studies have found that improvements in water quality result in increased benefits (19), consistent with estimates that Great Lakes restoration efforts could yield returns in excess of $50 billion beyond their costs (11).…”
Section: Resultsmentioning
confidence: 99%
“…4 C and D) requires further research to determine if these services would benefit from restoration or are sufficiently resilient to stress that restoration is unnecessary. However, beach closings (17), sport fishery declines (18), and other types of foregone recreational opportunities suggest that stressor mitigation could indeed enhance service provisioning. For example, a number of studies have found that improvements in water quality result in increased benefits (19), consistent with estimates that Great Lakes restoration efforts could yield returns in excess of $50 billion beyond their costs (11).…”
Section: Resultsmentioning
confidence: 99%
“…Predation on alewives by Chinook salmon in Lake Michigan has apparently increased during the 2000s, and this increased predation was likely responsible for the reduced adult alewife abundance observed during (Madenjian et al, 2010. A new source of wild Chinook salmon recruitment to Lake Huron, and presumably Lake Michigan as well, was activated sometime during the late 1990s or early 2000s (Johnson et al, 2010). In addition, the reduction in alewife energy density during the late 1990s was also expected to increase the predation rate on alewives by Chinook salmon in Lake Michigan during the 2000s .…”
Section: Complex Interactionsmentioning
confidence: 99%
“…Adlerstein et al (2007) found that 6% of coded-wire-tagged Chinook Salmon from Lake Huron were recovered in Lake Michigan during 1993-2001, whereas Adlerstein et al (2008) found no evidence of Lake Michigan Chinook Salmon recoveries in Lake Huron. Since wild Chinook Salmon production has remained high after the Alewife population collapse that occurred in Lake Huron soon thereafter (Johnson et al 2010), there is some concern that substantial numbers of Chinook Salmon are crossing the Straits of Mackinac into Lake Michigan to forage. Wild reproduction of Chinook Salmon also occurs in Lake Michigan, and though highly variable, in some years it has exceeded stocking levels .…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the decrease in Lake Michigan Alewife energy density, which probably occurred during the mid or late 1990s, could potentially lead to a substantial increase in the rate of Alewife consumption by Chinook Salmon . Finally, the surge in production of wild Chinook Salmon smolts originating from one tributary or set of tributaries to Georgian Bay of Lake Huron during the late 1990s or early 2000s, as documented by Johnson et al (2010) and Marklevitz et al (2011), may have led to a substantial increase in Chinook Salmon abundance in Lake Michigan between the 1994-1996 and 2009-2010 periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation